Assessment of energy output from corn waste using microbial fuel cells. - Genisan, Aleja N.
Microbial fuel cells (MFC) using accessible and affordable materials and without the use of any toxic mediators and using a pure culture of a facultative anaerobic bacteria, Enterobacter cloacae, were evaluated under neutral pH conditions and at room temperature (25-30 degrees Celcius). Power outputs were determined from pure corn waste of different concentrations and corn waste added with 50 ml E. cloacae inoculum for 20 days. Moreover, the effect of ammonia substrate laoding to bioelectricity output was also monitored for 14 days. Results showed that it is feasible to generate power from corn waste but maximum power output was observed using 15 g substrate concentration added with ammonia and E. cloacae inoculum.